On the Set of Fellini’s Movies: Investigating and Preserving Multi-Material Stage Costumes Exploiting Spectroscopic and Mass Spectrometric Techniques - Francesca Sabatini; Jacopo La Nasa; Camilla Guerrini; Francesca Modugno; Sara Bonadio; Federica Ursino; Isetta Tosini; Maria Perla Colombini; Ilaria Degano (Applied Sciences, 2021)
Since the second half of the 19th century, the world of textile production was radically changed both in terms of esthetics and of the performances leading to industrial products whose chemical properties were totally unknown and unexplored. Stage costumes are typical examples of multi-material art objects where different natural and synthetic materials were used to fulfil specific purposes. This research was performed in the framework of a diagnostic and restoration campaign of dresses of two Federico Fellini’s movies (“Il Casanova” and “Roma”). For the characterization of the textile fibers, Attenuated Total Reflection Fourier Transform Infrared Spectroscopy (ATR-FTIR) and Pyrolysis Gas Chromatography coupled with Mass Spectrometry (Py-GC/MS) were employed. The structure of the metallic threads was investigated by Scanning Electron Microscopy coupled with Energy-Dispersive X-ray Spectroscopy (SEM-EDX). Dye identification was carried out by High Performance Liquid Chromatography coupled with Diode Array Detector and mass spectrometry (HPLC-DAD, HPLC-ESI-Q-ToF). The analytical approach adopted allowed us to fully characterize the costumes composed of natural, synthetic and artificial fibers dyed with complex mixtures of last generation synthetic dyes. The results collected were fundamental to fine-tune an effective restoration aimed at minimizing the damages due to ageing, inaccurate home-made restoration interventions, or poor conservation conditions.